ANALYSIS OF STUDENT DIFFICULTIES IN SOLVING TRIGONOMETRIC PROBLEM - Yusuf Faturohman; Susan Amelia (KALAMATIKA Jurnal Pendidikan Matematika, 2020)
This study is done to explore learning difficulties when students are given trig problems in solving math problems. Learning difficulties that encounter during learning and results in less than optimal learning. Trigonometric materials given are just about the number and ratio of sine cosine. Trigonometric materials are given based on the results of a study in student mathematics problem. The ability to solve mathematical problems based on 4 indicators is to understand problems, plan ideas to use, solve problems and reexamine them. This research was tested in praise of the sophomores science class 2 MAN Cimahi. This method of research with qualitative research with students analyzes answer results. The results of this research have found some difficulty with learning problem-solving skills. As for the fourth problem he gave, many of the students had difficulty solving the trigonometry problem.